Adventures in chemical physics (Wiley, 2006)
Written for researchers and graduate students, each of the six articles of this volume provide an overview of a question or field, with discussion of its development and current state of research. The topics are dynamical models for two-dimensional infrared spectroscopy of peptides, energy transfer and photosynthetic light harvesting, second and first-order phase transitions in molecular nanoclusters, calculus for relating the dynamics and structure of complex biological networks, analysis and control of ultrafast dynamics in clusters, and ultracold large finite systems.